The role and targeting strategies of non-coding RNAs in immunotherapy resistance in oral squamous cell carcinoma - Liang, Zhinan; Zhao, Yicheng; Wang, Xin; Li, Yuehe (Frontiers in Cell and Developmental Biology, 2025)
Oral squamous cell carcinoma (OSCC) represents a major global health burden, with resistance to immune checkpoint inhibitors (ICIs) posing a significant barrier to effective immunotherapy. Emerging evidence implicates non-coding RNAs (ncRNAs)—including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs)—as pivotal regulators of this resistance. In this review, we discuss how ncRNAs contribute to OSCC immunotherapy resistance by modulating immune checkpoint expression, suppressing anti-tumor T cell function while promoting immunosuppressive Tregs, reprogramming the tumor microenvironment (TME) via metabolic remodeling and myeloid cell regulation, and enhancing intrinsic tumor resistance through epigenetic alterations and cancer stem cell activation. These multifaceted roles highlight the therapeutic potential of targeting ncRNAs. Strategies involve inhibiting oncogenic ncRNAs or restoring tumor-suppressive counterparts, facilitated by advanced delivery methods like nanoparticles or exosomes. Combining ncRNA-based therapies with ICIs offers a promising approach to overcome resistance. Key challenges remain, including precise functional annotation, efficient and specific delivery, experimental validation, biomarker identification, and the design of optimized clinical trials—potentially guided by artificial intelligence and multi-omics approaches. Ultimately, targeting the complex ncRNA networks may offer transformative improvements in immunotherapy outcomes for OSCC patients.